Analysis of Stability of Lubricating Oil Discharge Using the Individual Moving Range (IM-R) Chart Method - Ayu Nur Fithri; Gusmi Kholijah (Program Studi Matematika, Universitas Tadulako, 2025)
The stability of lubricant oil expenditure at PetroChina International Jabung Ltd with the aim of preventing dead stock. Dead stock is defined as material stock that has not been used or issued for more than five years. The existence of dead stock can lead to excess materials, which results in wasted costs. Specifically, if PetroChina experiences excess materials, the funds used to purchase lubricating oil will not be reimbursed by the state. The data used is oil lubricating production data for the period January 2022-December 2024 each month with a total of 36 observations. To analyze oil lubricating production stability, an Individual Moving Range (IM-R) chart is used, which is a Statistical Quality Control (SQC). The analysis results show several data points that are outside the control limits, indicating special cause variations in the oil lubricating production process. These uncontrolled points indicate that the process is not yet fully stable and can be influenced by factors outside of normal variations. The results of the study provide recommendations in the form of further investigation into the surge in oil lubricating production and optimizing demand planning through ROP/ROQ and SOQ to make oil lubricating production more consistent and avoid the risk of dead stock.